Melesatkan Kreativitas: Efektivitas Model PJBL Berbasis Poster dalam Mengasah Kemampuan Berpikir Kreatif Siswa pada PAI BP - Annisaul Khairat; Marwali Putra; Fauzia Amanda Putri (AS-SABIQUN, 2026)
The low level of students’ creative thinking skills in Islamic Religious Education and Character Education (PAI BP), which is still dominated by conventional teaching methods, indicates the need for innovative learning models that are more oriented toward creativity development. This study aimed to analyze the effect of a poster-based Project Based Learning (PjBL) model on improving students’ creative thinking skills in PAI BP. A quantitative approach was employed with a one-group pretest–posttest design, involving 26 Grade VIII students of UPT SMPN 3 Batipuh as the sample, determined using a saturated sampling technique. Data were collected using a creative thinking test instrument that had been empirically validated and shown to be reliable (Cronbach’s alpha = 0.892), and were analyzed using a paired samples t-test. The results showed a significant increase in creative thinking skills, as indicated by the rise in the mean score from 62.42 in the pretest to 89.62 in the posttest, with a difference of 27.20 points, and a test statistic (t_hit = −12.467; sig. = 0.000) confirming the acceptance of the alternative hypothesis. These findings indicate that the poster-based PjBL model is effective in enhancing students’ creative thinking skills in PAI BP. The implications of this study suggest that this model can serve as an innovative learning alternative that not only develops cognitive aspects and creativity but also strengthens students’ collaboration, communication, and visual skills, making it highly relevant for adoption in 21st-century competence-oriented instructional practices.